2004
DOI: 10.1111/j.1469-8749.2004.tb01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prognosis of cerebral venous sinus thrombosis in childhood

Abstract: Cerebral venous sinus thrombosis (CVST) is a rare but potentially serious disorder in children. There is no literature on the long‐term neuropsychological and emotional sequelae and implications for quality of life. We studied 17 children who had CVST after the neonatal period, aged between 1 month and 16 years at the time of CVST (mean age at CVST was 6 years, median 4 years 8 months). Five children died during follow‐up. The cause of death was related to CVST in one child. Twelve children participated in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Cognitive difficulties have been found to occur in almost 40% of children with CVST,1 while other studies have found fewer or no cognitive difficulties 18 19. In our series the most frequently occurring adverse outcome was chronic intracranial hypertension.…”
Section: Discussioncontrasting
confidence: 44%
“…Cognitive difficulties have been found to occur in almost 40% of children with CVST,1 while other studies have found fewer or no cognitive difficulties 18 19. In our series the most frequently occurring adverse outcome was chronic intracranial hypertension.…”
Section: Discussioncontrasting
confidence: 44%
“…Other predictors of poor neurologic outcome were coagulation abnormalities, multiple sinus thrombosis, seizures at presentation, and venous infarction 4950. Notably, CSVT prognosis was found to be better when compared to arterial ischemic stroke 5152. Nearly 50% of CSVT patients do not have infarcts and may suffer fewer motor deficits or no permanent damage 53…”
Section: Outcomementioning
confidence: 99%
“…On brain MRI performed in the third month in this patient, encephalomalacia was found, but neurological examination was found to be normal. In the pediatric age group, the mortality rate related with cerebral sinovenous thrombosis is below 10%, but neurological defects may be observed at the time of discharge or during the follow-up in 17-79% of the patients; long-term rehabilitation may be needed because of motor and cognitive sequelae (2,10,18,(32)(33)(34). Young age, coma, seizure and focal neurological findings have been found to be related with poor prognosis (2).…”
Section: Discussionmentioning
confidence: 99%